Financial Performance Analysis and Valuation of PT Indomobil Sukses Internasional Tbk in Comparison to Other Automobile Company; Tan Chong Motor Holdings Berhad - Pratama, Aditya; Nainggolan, Yunieta Anny (Journal of Business and Management, 2015)
Abstract-According to Bank Indonesia’s 2012 annual report, Indonesia’shousehold consumption and investment have been relatively high which have created a market opportunitiesfir domestic industry, in particular for automobile industry. Automobile industry has experienced a growth rate of 10% from 2012 to 2013, which was the highest growth percentage of automobile industry in Southeast Asia. Currently, one of the biggest players in Indonesia automobile industry is Indomobil (PT IMAS), which was established in 1976. Tan Chong, a Malaysia based automobile company is chosen to be the peer firm, due to its similar characteristics and the comparable market condition with Indomobil’s. This thesis examines the financial performanceof PT IMAS and Tan Chong from 2009 to 2014 using several method such as industry, Compound Annual Growth Rate (CAGR), cross-section analysis, DuPont formula analysis.This research also values those two companies using established valuation approaches such as relative multiple and discounted free cash flow model.Financial performance analysis shows that PT IMAShave been struggling while Tan Chong also came underperformed as shown by the unfavorable 2014 performance for both companies. This is due to competitive market environment and higher cost attributed to rough exchange rate condition. Multiple valuation and discounted cash flow models show that PT IMAS and Tan Chong overvalued. Therefore it is suggested that investors are advised to take caution on their investment decision onPT IMAS and Tan Chong and they are recommended to sell their shares in those company. Keywords: Automobile industry, financial performance,financial ratios, DuPont formula, Valuation